2008
DOI: 10.1136/bjo.2007.123513
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal bevacizumab for the treatment of macular oedema secondary to branch retinal vein occlusion

Abstract: Purpose: To evaluate the effect of intravitreal bevacizumab (Avastin) injections on visual acuity (VA) and foveal retinal thickness in patients with macular oedema secondary to branch retinal vein occlusion. Associated risk factors include advanced age (usually 60-70 years), arterial hypertension, arteriolosclerosis, diabetes mellitus, hyperlipidaemia and smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(63 citation statements)
references
References 17 publications
3
58
1
1
Order By: Relevance
“…Consequently, there have been other reports of short-term beneficial effect of intravitreal bevacizumab to treat macular oedema secondary to retinal vascular disease, including branch retinal vein occlusion 24,25 and diabetic retinopathy. 26,27 More recently, Ferrara et al 28 reported a dramatic improvement in the visual acuity and clinical fundus appearance with significant macular thickness reduction after the early intravitreal bevacizumab injections.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, there have been other reports of short-term beneficial effect of intravitreal bevacizumab to treat macular oedema secondary to retinal vascular disease, including branch retinal vein occlusion 24,25 and diabetic retinopathy. 26,27 More recently, Ferrara et al 28 reported a dramatic improvement in the visual acuity and clinical fundus appearance with significant macular thickness reduction after the early intravitreal bevacizumab injections.…”
Section: Discussionmentioning
confidence: 99%
“…Kreutzer et al 8 reported improvement in visual acuity from 0.79 (0.39) log MAR to 0.51 (0.34) log MAR at 6 months ( p ¼ 0.009). Kreichbaum et al 9 reported an increase in BCVA from a mean of 20/100 at baseline to 20/50 at 6 months.…”
Section: Discussionmentioning
confidence: 96%
“…The central macular thickness was more than 296 m in all patients based on Spectral domain OCT. Kreutzer et al have reported a mean decline in retinal thickness from 474 m at baseline to 316 m at 6 months. 8 Kreichbaum et al have reported a decrease of central macular thickness from 558 m at baseline to 382 m at 6 months with 3, one monthly injection. 9 In our study we found a decrease in central macular thickness from a mean of 586.30 m at baseline to a mean of 329.10 m at approximately 12e16 weeks, i.e.…”
Section: Discussionmentioning
confidence: 97%
“…diabetic macular edema, age related macular degeneration). Several studies have reported a decrease in retinal thickness and improved visual acuity after receiving bevacizumab (Kreutzer et al, 2008;Kriechbaum et al, 2008;Pai et al, 2007). Visual acuity usually increased to maximum in 3-6 weeks after the injections (Stahl et al, 2007).…”
Section: Sequelae Treatmentmentioning
confidence: 99%